Structural Damage Detection Using Modal Parameters and Particle Swarm Optimization - Gökdağ, Hakan; Yıldız, Ali Rıza (Carl Hanser Verlag, 2012)
Vibration based on structural damage detection (DD) is an important subject in many fields of engineering. Detection of possible damage locations before destructive stiffness losses in the engineering structures occur, is a main goal of DD. This paper describes the damage detection in structural elements by means of Particle Swarm Optimization algorithm (PSO). In this regard, the finite element model of a Timoshenko beam is considered, and damage is assumed as a stiffness loss in some elements. Damage locations and extents are identified minimizing some well-known modal parameter based objective functions. It is concluded that modal flexibility is the best among the considered damage indexes. Also, the results show that PSO is an effective optimization approach in structural damage detection.
Keywords: [No Keywords]